2016
DOI: 10.15252/emmm.201506031
|View full text |Cite
|
Sign up to set email alerts
|

Chronic miR‐29 antagonism promotes favorable plaque remodeling in atherosclerotic mice

Abstract: Abnormal remodeling of atherosclerotic plaques can lead to rupture, acute myocardial infarction, and death. Enhancement of plaque extracellular matrix (ECM) may improve plaque morphology and stabilize lesions. Here, we demonstrate that chronic administration of LNA‐miR‐29 into an atherosclerotic mouse model improves indices of plaque morphology. This occurs due to upregulation of miR‐29 target genes of the ECM (col1A and col3A) resulting in reduced lesion size, enhanced fibrous cap thickness, and reduced necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 48 publications
(64 reference statements)
1
58
0
Order By: Relevance
“…A previous study revealed that miR-29c was closely associated with atherosclerosis through several different mechanisms [26]. We found that miR-29c levels were higher in patients with increased CIMT than in those with normal CIMT values.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 52%
See 1 more Smart Citation
“…A previous study revealed that miR-29c was closely associated with atherosclerosis through several different mechanisms [26]. We found that miR-29c levels were higher in patients with increased CIMT than in those with normal CIMT values.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 52%
“…The phenotypic transformation and dysfunction of vascular smooth muscle cells, endothelial cells, and macrophages, such as abnormal proliferation and apoptosis, are a key pathological basis of atherosclerosis [29]. Previous studies have demonstrated that miR-29 regulates atherosclerosis by modulating miRNA targets that encode extracellular matrix proteins (e.g., collagen A and collagen 3A) [26]. Additionally, miR-29c could inhibit endotheliocyte migration and angiogenesis of human endothelial cells by suppressing the insulin like growth factor 1 [30].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Plasma miR-29a was a new biomarker that could play a role in the pathophysiology of atherosclerosis (Hulsmans and Holvoet 2013). Previous studies (Liu et al 2010;Maurer et al 2010;Kriegel et al 2012) have revealed that target genes of miR-29, such as type I and type III collagens, were important in the development of atherosclerosis (Ulrich et al 2016). The usage of miR-29 antagonists may prevent plaque remodelling (Ulrich et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies (Liu et al 2010;Maurer et al 2010;Kriegel et al 2012) have revealed that target genes of miR-29, such as type I and type III collagens, were important in the development of atherosclerosis (Ulrich et al 2016). The usage of miR-29 antagonists may prevent plaque remodelling (Ulrich et al 2016). Furthermore, a basic research demonstrated that the expression of Quaking protein was modulated by miR-29a and that inhibiting the expression of Quaking protein in turn resulted in downregulation of scavenger receptor A and lipid uptake, an important process involved in atherosclerosis (Wang et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…An example of a typical GO annotation for a biological process regulated by a miRNA, including contextual details describing the cell and tissue in which the process is being regulated, is shown in row 3 of Table 3. Priority is given to biological processes that will be most beneficial to therapeutic applications, and within the process-based approach, priority is given to miRNAs that are proposed to be therapeutic targets and which have been selected for clinical trial, e.g., miR-15, the inhibition of which was shown to protect against cardiac ischaemia damage (Hullinger et al 2012); miR-29, which is under investigation for stabilizing atherosclerotic plaques (Ulrich et al 2016), alleviating pulmonary fibrosis (Montgomery et al 2014) and providing a therapy for Duchenne muscular dystrophy (Heller et al 2017); miR-155, which is being investigated for treating T cell lymphoma (Seto et al 2015); and miR-208 under investigation for treatment of heart failure (Montgomery et al 2011). Occasionally, experimental information is lacking for a given human miRNA, therefore experimental evidence from a mammalian ortholog may be curated instead.…”
Section: Curation Of Mirna-regulated Pathways and Processesmentioning
confidence: 99%